COEXISTENCE OF FAMILIAL MEDITERRANEAN FEVER AND ANKYLOSING SPONDILITIS: A CASE REPORT - Sevtap Köksal Avcı; Nesibe Doğan; Hikmet Koçyiğit; Alev Gürgan (Archives of Rheumatology, 2005)
Familial Mediterranean fever (FMF) is a recurrent and self-limiting genetic disease characterized by irregular attacks of fever, peritonitis, pleurisy, arthritis and erysipelas-like rash. The most common type of articular involvement is acute monoarthritis. Arthritic episodes may be prolonged in about 5% of patients and hip and knee joints are frequently affected. Sacroiliitis and seronegative spondyloarthropathy (SNSA) may develop in some patients with FMF. A 23-year old man with FMF who was concomitantly diagnosed as ankylosing spondylitis according to the modified New York criteria is presented. Also the coexistence of FMF and SNSA, its treatment and amyloidosis which is the most serious complication of FMF is discussed with a review of the literature. As a result, we think that the possibility of development of SNSA during the follow-up of FMF patients should be kept in mind and symptoms should be evaluated carefully in this convern. Additionaly, the importance of daily regular use of colchicine and consideration of amyloidosis in the regular follow-up of FMF patients whether they have sacroileiitis or not have been emphasized.